Efficient Preamble Design Technique for Millimeter-Wave Cellular Systems with Beamforming - Dae Geun Han; Yeong Jun Kim; Yong Soo Cho (Sensors, 2016)
The processing time for beam training in millimeter-wave (mmWave) cellular systems can be significantly reduced by a code division multiplexing (CDM)-based technique, where multiple beams are transmitted simultaneously with their corresponding Tx beam IDs (BIDs) in the preamble. However, mmWave cellular systems with CDM-based preambles require a large number of cell IDs (CIDs) and BIDs, and a high computational complexity for CID and BID (CBID) searches. In this paper, a new preamble design technique that can increase the number of CBIDs significantly is proposed, using a preamble sequence constructed by a combination of two Zadoff-Chu (ZC) sequences. An efficient technique for the CBID detection is also described for the proposed preamble. It is shown by simulations using a simple model of an mmWave cellular system that the proposed technique can obtain a significant reduction in the complexity of the CBID detection without a noticeable performance degradation, compared to the previous technique.